Humanization and dehumanization: from Laclau, Mouffe and Schmitt to the Colombian armed conflict - Palma Álvarez, Daniel Arturo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
This paper analyses how dehumanisation presents itself in armed conflicts and tries to demonstrate that, in most cases, the ‘discursive’ and the ‘violent’ coexist so the ‘other’ is a blurred construction that changes according to the context. As a consequence, a clear division between ‘enemy’ and ‘adversary’ cannot be established, so it has to be accepted that this relationship is much more complex. For this analysis, the history of the Colombian armed conflict is revised from the mid-twentieth century, using Chantal Mouffe and Ernesto Laclau’s post-structuralist discourse theory, and Carl Schmitt’s concept of the ‘political’.